PENGARUH AUDIT TENUR, UKURAN KAP DAN UMUR LISTING, TERHADAP AUDIT REPORT LAG DENGAN SEPSIALISASI INDUSTRI AUDITO SEBAGAI MODERASI (Studi Empiris pada Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017) - Putri, Tri i Aulia; Anisma, Yuneita; Zarefar, Arumega (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to determine the effect of audit tenure, KAP size andlisting age to the audit report lag with auditor industry specialization as amoderate. The sample of this research at manufacturing companies that listed inthe Indonesian Stock Exchange (IDX) period 2015 to 2017. The sample of thisresearch is 195 financial statements from 65 nabufacturing companies. Samplesare used by purposive sampling method. Data analysis used multiple linearregression and moderated regression analysis method (MRA). Result of the testshowed that audit tenure, KAP size and lsting age an effect on audit report lag.This research find evidence that has interaction between KAP size with auditorindustry sepecialization an effect on audit report lag. The interaction betweenaudit tenure and listing age with auditor industry specialization had no effect onaudit report lag.Keywords : Audit Tenure, KAP Size, Listing Age, Audit Report Lag, AuditorIndustry Specialization